West Bank and Gaza : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This CFAA is able to report major improvements in the public financial management (PFM) system of the West Bank and Gaza (WB&G) in the period since mid-2002. Recent areas of improvement are in budgeting (both development and execution) and in fiscal transparency. Other PFM include the following: 1) All Palestinian Authority (PA) revenues are now paid into the Central Treasury Account (the CTA), a single treasury account which brings together all government revenues and provides a single pool of funds out of which all expenditures are paid. 2) An orderly system of budgetary appropriation is now in force. 3) Reflecting these new and improved processes, the budget speeches and extensive background budget data are posted on a regular basis on the Ministry of Finance's (MOF) external website, itself a symbol of a new approach to transparency and improved budget management. 4) MOF is exercising firm control over budget expenditures - with the obvious caveat that the chronic post-September 2000 shortage of Budget funds has led to strict limits on non-wage expenditures and to continuous ad hoc adjustments, with h d s often being released by MOF on a daily basis. One consequence of chronic revenue shortage and the erratic nature of donor budget support has been a periodic accumulation of expenditure arrears to the PA's pension funds, to commercial suppliers. These arrears and the short-term commercial bank debt that MOF has also contracted are, however, being transparently handled. The IMF is also regularly monitoring budget execution and the arrears and debt situation. 5) Monthly budget execution reports are now being prepared and posted on MOF's external website within a few days of the end of each month. 6) A program of placing in each ministry financial controllers who report to MOF has been initiated. 7) The MOF has launched a program to develop an ex post internal audit department in MOF. 8) Control over the civil service payroll has improved significantly. 9) In the 2004 Budget, the previous large discretionary transfer appropriation for the President's Office has been virtually eliminated with these funds instead transferred to relevant service ministries (Health, Education and Social Affairs). 10) The establishment of the Palestine Investment Fund (PIF) has brought all PA equity holdings, including virtually all state-owned enterprises (SOEs), under MOF oversight and within a centralized and commercially oriented management framework. 11) Measures have been taken to reduce PA monopolistic activities in the importation of cement, while the management of the Petroleum Commission has been taken over directly by MOF. On the basis of these improvements, and of Palestinian Authority (PA) commitment to further reforms, the World Bank is able to support a program of general donor budget support to the PA. However, the CFAA also identifies "residual weaknesses" in financial accountability, which relate to the lack of adequate public aggregate financial statements, inadequate auditing, and the undeveloped oversight role of the Palestinian Legislative Council (PLC). The report discusses a significant number of actions, which still need to be implemented and notes that most of the essential steps are either under implementation by the PA, or are planned.